ANALYSIS OF THE RESULTS OF PHYSICAL AND MATHEMATICAL MODELING AND SEPARATION OF SUNFLOWER SEED MATERIAL (Collection of research papers «PROGRESSIVE TECHNIQUE AND TECHNOLOGIES OF FOOD PRODUCTION ENTERPRISES, CATERING BUSINESS AND TRADE», 2026)
The issue of mathematical modeling of the movement of a ball between the working planes of a vibropneumatic separator in two cases is considered. The first case is considered if, upon impact, there is sliding of the ball along the surface and its stopping. The second case is considered if, upon impact, there is exclusively sliding without stopping until the moment of rebound of the ball from the surface. The method of constructing the trajectory of the ball's movement in the working channel of the separator is considered, in order to determine the distance of movement of a particle of the seed mixture along the working channel of the vibropneumatic separator and, based on these values, to determine the receiver of the separation products to which the particle will fall. The change in the air flow velocity in the working channel of the separator and the modernized separator equipped with a louvered air flow distributor along its height and length is investigated.Comparative analysis revealed the design shortcomings of the non-modernized separator and proved the advantages of the modernized separator in the formation of a more stable and uniform air flow in the working channel of the separator. The formation of the air flow in the working channel of the vibro-pneumatic separator is performed by a mechanism with louvers and plates. In turn, the louvers form the required air flow, and the plates prevent the formation of turbulence at the outlet of the mechanism.Studies of the process of separation of sunflower seed material were carried out, which confirm the effectiveness of the proposed design of the modernized vibro-pneumatic separator. Comparative analysis revealed the correspondence of the results of mathematical modeling to the results of separation of sunflower seed material on the modernized vibro-pneumatic separator.
Keywords: vibropneumatic separator; mathematical modeling; air flow velocity; sunflower seeds